KAJIAN HUKUM HAK PENCIPTA ATAS LAGU CIPTAAN YANG TELAH DIPERJANJIKAN PADA PIHAK PERUSAHAAN REKAMAN (PUTUSAN MAHKAMAH AGUNG 254K/PDTSUS/2009) - RETTA SITORUS (PREMISE LAW JURNAL, 2016)
Copyright as a part of HaKI (Intellectual Property Rights) is very personal and exclusive rights for composer or holder of a copyright to announce or distribute his creation without reducing any limitation according to the prevailing regulations. The thesis uses judicial normative and descriptive analytic methods. Copyright is in the hand of the composer although it has been given to another party. Besides that, it is prohibited to change the title and subtitle although it has been given to another party. Legal consideration of the Supreme Court in copyright dispute in the Ruling No. 254K/PDTSUS/2009 states that the transferring or being transferred of copyright has to be done in specific way by its composer and user, and the license has to be signed by the composer although it has been in the hand of another party. Keywords: Copyright on Song, Contract, Sound Recording Firm